The impact of systematized physical activity on parameters of health-related physical fitness in schoolchildren aged 8 to 11 years - Marcelo José Resende Gonçalves; Camila Ramos Santos; Carla Cristiane Silva (Revista Brasileira de Atividade Física e Saúde)
It is recommended that proper incorporation of healthy habits of physical activity in childhood and adolescence has a positive impact on a physically active lifestyle in adult life. Thus, the present study aimed to verify the effects of four weeks of systematized physical activity in addition to the classes of Physical Education on parameters of physical fitness related to health of children and adolescents. The sample was selected by convenience and composed of 73 children and adolescents aged 8-11 years. The subjects were subdivided into 2 groups; one group of children exclusively attending Physical Education classes (PEC); and another group that performed Systematized Physical Activity (SPA). The following tests were applied; the abdominal test to assess strength and muscle resistance; the Paccer to verify cardiorespiratory fitness; and the adapted sit-and-reach to evaluate flexibility. In addition, the Body Mass Index (BMI) and relative fat (%F) were assessed. Sample characterization data and motor tests are presented as median and interquartile range. The ANOVA test of repeated measurements was used to verify the effect of the moments. The results pre training did not demonstrate differences between groups in measures of body mass, stature, BMI, or motor tests. The effects of physical training were observed in all motor tests in favor of the SPA, while the PEC did not demonstrate significant differences between moments. In conclusion, four weeks of additional systematized physical activity promoted a significant positive effect in motor tests applied with a focus on heath.